A fuzzy association rule-based knowledge management system for occupational safety and health programs in cold storage facilities. Issue 2 (14th May 2018) - Tsang, Y.P.; Choy, K.L.; Koo, P.S.; Ho, G.T.S.; Wu, C.H.; Lam, H.Y.; Tang, Valerie
Abstract : Purpose: This paper aims to improve operational efficiency and minimize accident frequency in cold storage facilities through adopting an effective occupational safety and health program. The hidden knowledge can be extracted from the warehousing operations to create the comfortable and safe workplace environment. Design/methodology/approach: A fuzzy association rule-based knowledge management system is developed by integrating fuzzy association rule mining (FARM) and rule-based expert system (RES). FARM is used to extract hidden knowledge from real operations to establish the relationship between safety measurement, personal constitution and key performance index measurement. The extracted knowledge is then stored and adopted in the RES to establish an effective occupational and safety program. Afterwards, a case study is conducted to validate the performance of the proposed system. Findings: The results indicate that the aforementioned relationship can be built in the form of IF-THEN rules. An appropriate safety and health program can be developed and applied to all workers, so that they can follow instructions to prevent cold induced injuries and also improve the productivity. Practical implications: Because of the increasing public consciousness of occupational safety and health, it is important for the workers in cold storage facilities where the ambient temperature is at/below 10°C. The proposed system can address the social problem and promote the importance of occupational safety and health in the society. Originality/value: This study contributes to the knowledge management system for improving the occupational safety and operational efficiency in the cold storage facilities.